Effects of capecitabine treatment on the uptake of thymidine analogs using exploratory PET imaging agents: 18F-FAU, 18F-FMAU, and 18F-FLT. Issue 1 (December 2016) - McHugh, Christopher; Lawhorn-Crews, Jawana; Modi, Dipenkumar; Douglas, Kirk; Jones, Steven; Mangner, Thomas; Collins, Jerry; Shields, Anthony
Abstract Background A principal goal for the use of positron emission tomography (PET) in oncology is for real-time evaluation of tumor response to chemotherapy. Given that many contemporary anti-neoplastic agents function by impairing cellular proliferation, it is of interest to develop imaging modalities to monitor these pathways. Here we examined the effect of capecitabine on the uptake of thymidine analogs used with PET: 3'-deoxy-3'-[18 F]fluorothymidine (18 F-FLT), 1-(2'-deoxy-2'-[18 F]fluoro-β-D-arabinofuranosyl) thymidine (18 F-FMAU), and 1-(2'-deoxy-2'-[18 F]fluoro-β- D-arabinofuranosyl) uracil (18 F-FAU) in patients with advanced cancer. Methods Fifteen patients were imaged, five with each imaging agent. Patients had been previously diagnosed with breast, colorectal, gastric, and esophageal cancers and had not received therapy for at least 4 weeks prior to the first scan, and had not been treated with any prior fluoropyrimidines. Subjects were imaged within a week before the start of capecitabine and on the second day of treatment, after the third dose of capecitabine. Tracer uptake was quantified by mean standard uptake value (SUVmean ) and using kinetic analysis. Results Patients imaged with18 F-FLT showed variable changes in retention and two patients exhibited an increase in SUVmean of 172.3 and 89.9 %, while the other patients had changes ranging from +19.4 to -25.4 %. The average change in18 F-FMAU retention was 0.2 % (range -24.4 to 23.1) and18 F-FAU was -10.2 % (range -40.3 to 19.2). Observed changes correlated strongly with SUVmax but not kinetic measurements. Conclusions This pilot study demonstrates that patients treated with capecitabine can produce a marked increase in18 F-FLT retention in some patients, which will require further study to determine if this flare is predictive of therapeutic response.18 F-FAU and18 F-FMAU showed little change, on average, after treatment.